Indium-Mediated Blaise-Type Reaction of Bromomalonates with Nitriles and Isocyanates - Babaoglu, Emre; Harms, Klaus; Hilt, Gerhard (Synlett, 2016)
The indium-mediated Blaise-type reaction of bromomalonates with nitriles and isocyanates is described. The choice of the solvent is crucial for the successful reaction; the dependency on dichloromethane proved to be nonplussed. The reaction with nitriles led to the corresponding β-enamino diesters in moderate to good yields. The conversion with isocyanates generated carbamoyl malonates in good to excellent yields. Both reactions tolerated various functional groups regarding the electronic nature. Also, steric hindrance in the starting materials, as caused by mesityl isocyanate or diisopropyphenyl isocyanate, was well tolerated. In addition, a sequential three-component one-pot reaction sequence is described for the formation of 2,4-dioxo-1,2,3,4-tetrahydropyrimidine-5-carboxylates enabling future investigations in this field.
Keywords: Blaise reaction; bromomalonates; indium; isocyanates; nitriles; pyrimidines